The impact of lifetime PTSD on the seven-year course and clinical characteristics of OCD. (December 2017) - Ojserkis, Rachel; Boisseau, Christina L.; Reddy, Madhavi K.; Mancebo, Maria C.; Eisen, Jane L.; Rasmussen, Steven A.
Abstract: Research has suggested that the co-occurrence of PTSD in individuals with OCD is associated with more severe symptoms and less responsivity to empirically supported treatment as compared to individuals with OCD and no history of PTSD. However, much of this work has been limited by non-empirical case report design, cross-sectional and retrospective analyses, or small sample sizes. The current study extended this research by comparing the clinical characteristics of individuals with OCD with and without a lifetime PTSD diagnosis in a large, naturalistic, longitudinal sample over the course of seven years. At baseline, individuals with comorbid lifetime PTSD reported significantly more severe symptoms of OCD (including symptom levels and insight), lower quality of life, and higher rates of comorbid lifetime mood and substance use disorders than participants without lifetime PTSD. Further, individuals with comorbid OCD and lifetime PTSD reported significantly more severe OCD symptoms over the course of seven years than those without lifetime PTSD. These results are largely consistent with the existing literature and support the need to consider PTSD symptoms in the assessment and treatment of OCD. Highlights: Patients with OCD and PTSD had more severe OCD symptoms than those without PTSD. The group with PTSD had more mood and substance use disorders than without PTSD. The comorbid group had a more severe 7-year OCD course than those without PTSD.